Community Engagement in Supporting Measles Vaccination for Disease Prevention in the Selayar Islands - Resty Amalia Putri; Hadriyanti Syam; Nur Aisyah Nasir (FKM UIN Sumatera Utara Medan, 2026)
Infectious diseases remain a major public health problem in Indonesia, especially in archipelagic and remote areas such as the Selayar Islands. Limited access to health services, low public knowledge, and misinformation about vaccines often affect community participation in vaccination programs. This community service activity focuses on strengthening the role of the community in supporting vaccination as an effort to prevent infectious diseases. The aim of this activity was to increase community knowledge, attitudes, and participation regarding vaccination. This program used a participatory approach through Participatory Action Research (PAR) combined with Community Based Participatory Research (CBPR) and Asset Based Community Development (ABCD). The activity was conducted in Bontotangnga Village, Bontoharu District, Selayar Islands, involving 50 community members selected through purposive sampling. The intervention was carried out through health education, interactive discussions, and mentoring activities involving health cadres and community leaders. Data were collected using pre-test and post-test questionnaires, observation of participation, and short interviews. The results showed a significant increase in community knowledge and attitudes toward vaccination. The average knowledge score increased from 56.4% before the intervention to 82.7% after the intervention. Positive attitudes toward vaccination increased from 48% to 84%, and community participation reached 86%. In conclusion, community-based education and mentoring effectively improve public understanding and support for vaccination programs. Community involvement plays an important role in increasing participation in vaccination to prevent infectious diseases.